Application of Oxytocin Massage on Post-Partum Mothers to Increase Breast Milk Production - Wanda Youvada; Winarsih Nur Ambarwati (Indonesian Journal of Global Health Research, 2026)
During the postpartum period, mothers experience various physiological changes, including a decrease in progesterone levels and an increase in prolactin hormone after childbirth, which initiate the lactation process. Physical changes related to lactation include breast enlargement as a sign of breast milk production. Breast milk (ASI) is the best nutrition for newborns up to six months of age because infants’ digestive systems are not yet able to process foods other than breast milk. Inadequate breast milk production may lead to failure of exclusive breastfeeding, which can result in digestive disorders and decreased immunity in infants. One non-pharmacological intervention that can help stimulate breast milk production is oxytocin massage. This study aimed to determine the effect of oxytocin massage on breast milk production in postpartum mothers. This study employed a case study method involving two postpartum mothers as respondents. The intervention was conducted for three consecutive days with a frequency of two sessions per day and a duration of 10–15 minutes per session. Data were collected through interviews, observation, and documentation to obtain subjective and objective data on breast milk production before and after the oxytocin massage intervention. The collected data were analyzed descriptively by comparing breast milk production before and after the intervention and presented in narrative form. On the first day of oxytocin massage, both respondents showed no significant changes in breast milk production. However, after the intervention on the second and third days, an increase in breast milk production was observed, as indicated by fuller breasts, smoother milk flow, and infants appearing satisfied after breastfeeding. Breast milk production increased after the oxytocin massage intervention. Therefore, oxytocin massage can be considered an effective nursing intervention to support breastfeeding, particularly during the postpartum period.